PET Imaging of Serotonin Transporters with [11C]DASB: Test-Retest Reproducibility Using a Multilinear Reference Tissue Parametric Imaging Method - Kim, Jae Seung; Ichise, Masanori; Sangare, Janet; Innis, Robert B (The Journal of nuclear medicine (1978), 2006)
Parametric imaging of serotonin transporters (SERT) with 11C-labeled 3-amino-4-(2-dimethylaminomethyl-phenylsulfanyl)benzonitrile ([11C]DASB) PET is a useful data analysis tool. The purpose of this study was to evaluate the reproducibility of measurements of SERT binding potential (BP) and relative blood flow (R1) by a 2-parameter multilinear reference tissue parametric imaging method (MRTM2) for human [11C]DASB studies. Eight healthy subjects (3 men, 5 women; age, 26 +/- 9 y) underwent 2 [11C]DASB PET scans separated by 1 h on the same day (dose, 703 +/- 111 MBq). Parametric images of BP and R1 were generated by MRTM2 using the cerebellum as a reference region. The k'2 (clearance rate constant from the reference region) required by MRTM2 was estimated by the 3-parameter MRTM. Reproducibility of BP and R1 measurements was evaluated by calculating bias (100 x (retest - test/test), variability (SD of the bias), and reliability (intraclass correlation coefficient = rho) for several representative regions of interest (ROIs). BP and R1 were estimated for ROI time-activity curves fitted by MRTM2 and were compared with those based on the parametric images. The test-retest (0.066 +/- 0.013/0.06 +/- 0.011 min(-1)) MRTM k'2 reproducibility was excellent with small bias (3%) and variability (6%) and high reliability (0.95). Retest BP values were consistently lower than those of test BP values in all regions (a mean negative bias of approximately 6%; P < 0.001). The test-retest BP variability was relatively small, ranging from 4% to 13%, with rho ranging from 0.44 to 0.85. In contrast to BP, test-retest R1 values were similar with negligible bias of < or =0.1%. The test-retest R1 variability was excellent and smaller than that of BP ranging from 3% to 6%, with rho ranging from 0.58 to 0.95. BP and R1 values estimated by the ROI time-activity curve-fitting method were slightly lower ( approximately 3% and approximately 1%, respectively) than those by the parametric imaging method (P < 0.001). However, the test-retest bias and variability of BP and R1 were very similar for both ROI and parametric methods. Our results suggest that [11C]DASB parametric imaging of BP and R1 with the noninvasive MRTM2 method is reproducible and reliable for PET studies of SERT.